The elemental leader : unlocking your potential through values, perseverance, adaptability, and innovation - Comeau, Tyler (Productivity Press, 2026)
This book is a comprehensive leadership development book that reimagines the classical elements of Earth, Air, Water, and Fire as metaphors for effective leadership principles. The project focuses on helping leaders unlock their leadership potential by grounding their practices in these elemental principles. Each element represents a principle. Earth symbolizes core values and grounded mindsets, Air relates to overcoming adversity and perseverance, Water embodies adaptability and change processes, and Fire represents innovation, motivation, decision-making, and risk management. The book weaves personal anecdotes, case studies, supporting research, and actionable strategies to provide a holistic guide for leadership growth. The structure of the book is built around four major chapters, each dedicated to one of the elements. Within each chapter, the content is organized into multiple case studies of real-world leaders. For example, the Earth chapter analyzes Howard Schultz's leadership at Starbucks and Indra Nooyi's value-driven leadership at PepsiCo. Each case study includes sections on the relevance (why it matters), supporting research, and actionable strategies. This bridges the theoretical world with the practical application of lived experiences. Readers are encouraged to take part in the interactive tasks within each chapter for the purpose of optimizing their organizations. Key benefits of the book include the ability to integrate timeless principles with contemporary leadership challenges. By drawing on the elements, the project offers leaders a framework for making decisions that are both ethical and effective. From focusing on core values (missions, visions, etc.) to build resilience based on trust, to transparent communication when facing adversity as a highly effective team, to preparing teams for change (both expected and unexpected), and to igniting passion and driving for innovative and collaborative risk management, the chapters offer a balanced approach to leadership that is adaptable across various fields.In addition, the project stands out for its integration of reflective exercises and research-backed strategies. Leaders are invited to refine their approaches using the tools and strategic planning templates provided. This combination makes the project an indispensable guide for those looking to lead with authenticity and impact. Moreover, its diverse range of case studies allows readers to draw insights from leaders across industries, making the lessons ubiquitous and implementable in a variety of organizations.
Keywords: Four elements (Philosophy); Leadership.; elektronické knihy; electronic books